2019
DOI: 10.3892/ol.2019.10905
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic value of the BEX family in lung adenocarcinoma

Abstract: Previous studies have demonstrated that members of the brain-expressed X-linked (BEX) family participate in a wide range of biological functions in normal and tumor tissues. However, their role and clinical significance in lung adenocarcinoma (LUAD) remains unclear. The present study investigated The Cancer Genome Atlas data and revealed that the BEX family was downregulated in LUAD tissues compared with adjacent non-cancerous tissues. Additionally, analysis of LUAD cohorts from the Oncomine database revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…BEX5 , a member of the BEX family, is involved in various biological functions related to normal and tumor tissues ( 27 ). A previous study demonstrated that BEX5 mRNA levels are downregulated in LUAD tissues and have prognostic value ( 28 ). CD69, a C-type lectin receptor family member, is the earliest surface antigen expressed after T lymphocyte activation and acts as a co-stimulatory signal to promote further activation ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…BEX5 , a member of the BEX family, is involved in various biological functions related to normal and tumor tissues ( 27 ). A previous study demonstrated that BEX5 mRNA levels are downregulated in LUAD tissues and have prognostic value ( 28 ). CD69, a C-type lectin receptor family member, is the earliest surface antigen expressed after T lymphocyte activation and acts as a co-stimulatory signal to promote further activation ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] PDCD6 was also found to substantially expand in primary breast cancer tissues compared with para cancerous tissues, and it is correlated with lymph node metastasis and related to a low overall survival time. [ 9 ] Wang et al. demonstrated that PDCD6 collaborates with C‐Raf to facilitate colorectal cancer (CRC) progression through targeting Raf/MEK/ERK axis.…”
Section: Discussionmentioning
confidence: 99%
“…BEX family, containing BEX1, BEX2, BEX3, BEX4 and BEX5, had similar sequence and adjacent location with TCEAL family, which formed the BEX/TCEAL transcriptional regulator cluster [24]. BEX family proteins are known to play a role in neuronal development and recent studies suggest a role in cancers [25][26][27][28][29]. BEX1 suppressed tumor cell growth of esophageal squamous cell cancer, colorectal cancer, acute myeloid leukemia, oral squamous cell carcinoma, malignant glioma [30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%